Miejsce i znaczenie terenów zieleni miejskiej = Green areas - their role and importance in the cities - Asani, Anna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The article present specification of definition of municipal green areas. The characteristic of municipal green areas has been presented. The role of areas designing are set together
Keywords: 4 Międzynarodowa konferencja "Ochrona i rekultywacja terenów dorzecza Odry: rekultywacja terenów zdegradowanych" (28-29.06.2007); tereny zieleni; zieleń miejska; rola zieleni w miastach; green areas; municipal green; importance in the cities